Horizontal and vertical spatial variability analysis of soil attributes and their relevance to natural park chico mendes, sp, brazil - Simonetti, Vanessa Cezar [UNESP]; Sabonaro, Débora Zumkeller; Lourenço, Roberto Wagner [UNESP]; Rosa, André Henrique [UNESP]; Da Cunha E Silva, Darllan Collins [UNESP] (Revista Brasileira de Geografia Fisica, 2019)
Maintenance of environmental quality depends on intrinsic relationships between environmental compartments. Thus, the maintenance of preserved green spaces and proper soil management can contribute to quality of life of the population. Therefore, in this study was evaluated a spatial horizontal and vertical heterogeneity of the soil elements of the Natural Park Chico Mendes, from the perspective of the importance of urban parks for maintaining environmental quality and soil conservation. For this, three zones of the park with distinct phytophysiognomies were analysed, being conserved forest zone (ZMC); zone of forest (ZM) and zone of eucalyptus (ZE). The physicochemical analyses were extracted in depths 0-20 cm, 20-40 cm and 40-60 cm, according to the methodologies of the Agronomic Institute of Campinas (IAC) and EMBRAPA. The data spatialization was performed in the software ArcGis by the Inverse Distance Weighting (IDW) method. The results demonstrated the spatial heterogeneity of soil chemical attributes in different vegetation types of the park revealing that even areas with small extensions can show significant differentiation physico-chemical attributes, corroborating the importance of obtaining an appropriate soil management for the maintenance of environmental quality.
Análise da Variabilidade Espacial Horizontal e Vertical dos Atributos do Solo e sua Relevância para o Parque Natural Chico Mendes, SP
Keywords: Principal component analysis; Soil management; Spatial analysis; Urban parks